A survey of Culicidae (Insecta Diptera) in some habitats in Souk-Ahras province (Northeast Algeria) - Hafs, N.,H; Hamaidia,K; Barour,Choukri; Soltani,N (My University, 2021)
A survey of immature Culicidae was conducted in diverse habitats of Souk-Ahras province (Northeast Algeria) between December 2018 and November 2019. Altogether, 12,861 specimens were collected and identified. Nineteen species of mosquitoes, belonging to two main subfamilies viz. Culicinae (accounts for 84.21 %) and Anophelinae (as 15.79 %), under 5 genera (Culex, Culiseta, Anopheles, Aedes and Uranotaenia). Among identified species, six were mentioned for the first time in the province of Souk-Ahras. The predominant species of the total mosquito fauna was Cx. pipiens L. with an abundance rate of 69.63 %. Two habitats were characterized by the highest prevalence of 11 species, Taoura (with 1 spp. Anophelinae, 10 spp. Culicinae) and Sedrata (with 11 spp. of Culicinae). However, Souk-Ahras site contained the largest abundance (41.20 %) belonging to 6 species. In addition, the spatial distribution of mosquitoes according to climatic factors (temperature, rainfall, humidity) was discussed. Data supported by some ecological indices of composition and structure revealed that the diversity level in Souk-Ahras province was between medium and very low compared to a scale varied between 0 and 1 (global Simpson index 0.50). The most diversified site in species was Taoura with the highest Shannon index value (2.11). Since vectors occurrence is constantly changing, it will be suggested that mosquito control should be intensified within other potential breeding sites in northeastern Algeria